Therapy with bone marrow mesenchymal stem cells in bone regeneration in children with osteonecrosis secondary to sickle cell disease - Teixeira, Thiago Rhangel Gomes; Daltro, Gildásio de Cerqueira; Sberge, Fernando Luis; Barreto, Eduardo Silva Reis; Silva, Antônio Ferreira da (Frontiers in Cell and Developmental Biology, 2024)
This study aimed to describe the evolution of bone regeneration in children with hip osteonecrosis associated with sickle cell disease, treated with bone marrow-derived mesenchymal stem cell implants at the Professor Edgar Santos University Hospital Complex. Materials and methods: A non-randomized clinical trial was conducted with 48 patients of both sexes, aged between 11 and 18 years, diagnosed with femoral head osteonecrosis secondary to sickle cell disease. Patient selection was based on strict criteria, including confirmed diagnosis of sickle cell anemia and a stage of osteonecrosis compatible with the proposed treatment. Bone regeneration assessment was performed through radiographic examinations and magnetic resonance imaging, following the Ficat & Arlet criteria and the Salter-Thompson classification. Results: Statistical analysis revealed a significant association between the patients' age and positive treatment outcomes, suggesting that autologous bone marrow cell implantation is a safe and effective approach in the early stages of osteonecrosis. The majority of patients (87.5%) reported complete pain relief, while 10.42% experienced significant symptom improvement. Only one patient (2.08%) did not observe improvement. The results indicate that cell therapy can regenerate or slow the progression of bone necrosis, reducing the need for more invasive surgical procedures. Conclusion: The study demonstrates the potential of bone marrowderived mesenchymal stem cell implantation in treating hip osteonecrosis in children with sickle cell disease, emphasizing the importance of long-term monitoring of bone structure stability.